Information communications technology in general practice: cross-sectional survey in London - Zoe Keddie (Journal of Innovation in Health Informatics, 2005)
Objective To determine the prevalence of use of a range of information and communications technology (ICT) applications in general practice in London, UK. Design Cross-sectional postal questionnaire study. Participants 996 general practitioners (GPs) working in 32 primary care trusts (PCTs) in London. Main outcome measures Rates of self-reported use of paperless, paper-light and paper-based consultations in general practice, perceived barriers and facilitating factors relating to their use and current use or interest in using innovative ICT. Results Questionnaires from 520 respondents (52%) were analysed. A computer was used in clinical consultations by 95% of respondents; 34% operated paper-light consultations, and 41% paperless consultations. An electronic record was always used in 76% of consultations and paper records were never used in 19%. Paper-light and paperless consultations were conducted more frequently in larger practices and those in more affluent PCTs. Numerous barriers to the implementation of ICT were identified, including lack of time, lack of training resources and negative attitudes to computers. Personal digital assistants were used by 18% of respondents and 72% were interested in their use in the future. Conclusion We have shown that there has been a considerable increase in the rate of use of ICT in general practice in recent years, but these rates have fallen behind targets set by the NHS IT Strategy. Numerous barriers to the implementation of ICT exist, and further research is needed into means of overcoming them and on the evaluation of computer- supported consultations and other technologies in primary care.